Technological measures of copyright protection: using problems - Сопілко, І. М.; Пономаренко, О. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article examines the main technological measures of copyright protection on the Internet. Also, theauthors analyze the features of technical facilities and made their classification.